Magnetically separable ZnO/ZnFe204 and ZnO/CoFe204 photocatalysis supported onto nitrogen doped graphene for photocatalytic degradation of toxic dyes - Chandel, Naresh; Sharma, Kirti; Sudhaik, Anita; Raizada, Pankaj; Hosseini-Bandegharaei, Ahmad; Thakur, Vijay Kumar; Singh, Pardeep (Elsevier, 2019)
Advanced oxidation processes (AOPs) counting heterogeneous photocatalysis has confirmed as one of the preeminent method for waste water remediation. In the present work, we have successfully fabricated novel visible-light-driven nitrogen-doped graphene (NG) supported magnetic ZnO/ZnFe2O4 (ZnO/ZF/NG) and ZnO/CoFe2O4 (ZnO/CF/NG) nanocomposites. ZnO synthesized via direct precipitation method. Hydrothermal method was used for the preparation of nitrogen-doped graphene supported magnetic ZnO/ZF (ZnO/ZnFe2O4) and ZnO/CF (ZnO/CoFe2O4) nanocomposites. The procured materials were scrutinized by assorted characterizations to acquire information on their chemical composition, crystalline structure and photosensitive properties. The absorption and photocatalytic performance of photocatalysts were studied via UV–Visible spectra. Photodegradation performance of the synthesized nanocomposites was estimated toward mineralization of methyl orange (MO) and malachite green (MG) dyes in aqueous solution. The high surface area of ZnO/ZF/NG and ZnO/CF/NG was suitable for adsorptive removal of MO and MG dyes. The photodegradation performance of heterojunction photocatalysts was superior to bare photocatalyst in 140 min under visible-light irradiation. Spectrophotometer, GC–MS (Gas chromatography–mass spectrometry) elucidation was carried out to expose the possible intermediates formed. Both ZnO/ZF/NG and ZnO/CF/NG were rapidly isolated from the aqueous phase by applying an external magnetic field in 20 sec and 2 min, respectively. The photocatalytic performance and stability of ZnO/ZF/NG and ZnO/CF/NG nanocomposites were confirmed by conducting 10 consecutive regeneration cycles. Owing to recyclability of ZnO/ZF/NG and ZnO/CF/NG, these heterogeneous nanocomposites might be used as cost-effective for treatment of discarded water. The observations endorse that the synthesized ternary heterogeneous nanocomposites facilitates wastewater decontamination using photocatalytic technology.
Keywords: ZnFe2O4CoFe2O4; Nitrogen doped graphene; Supported photocatalysis Magnetic separation; Recycle efficiency; Dye mineralization